2021
DOI: 10.1136/bmjpo-2021-001042
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body ingestion during the COVID-19 pandemic: a retrospective single centre review

Abstract: IntroductionDuring the COVID-19 pandemic in 2020, there were many changes in the provision of healthcare as well as home and educational environments for children. We noted an apparent increase in the number of children presenting with ingested foreign bodies and due to the potential impact of injury from this, further investigated this phenomenon.MethodUsing a prospective electronic record, data were retrospectively collected for patients referred to our institution with foreign body ingestion from March 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
3
13
2
Order By: Relevance
“…The findings in our study compliment the pandemic patterns of FBI noted separately by Pizzol et al and Festa et al in single pediatric referral centers in the US and United Kingdom, respectively ( 16 , 17 ). Our multicenter analysis enhances the robustness of available evidence to support the protection of children from dangerous FBI.…”
Section: Discussionsupporting
confidence: 92%
“…The findings in our study compliment the pandemic patterns of FBI noted separately by Pizzol et al and Festa et al in single pediatric referral centers in the US and United Kingdom, respectively ( 16 , 17 ). Our multicenter analysis enhances the robustness of available evidence to support the protection of children from dangerous FBI.…”
Section: Discussionsupporting
confidence: 92%
“…BBs are commonly found in the household and in children, 62% of BBs were obtained directly from toys or other household objects, 30% were loose or intended for disposal, and 8% were obtained directly from packaging 2,3 . More recently, studies from around the world have shown an increase in BB ingestion during the COVID‐19 pandemic likely in part due to children being home and caregivers who must divide their attention between childcare and work‐from‐home duties 7,8,18,19 . Oesophageal impaction times are often prolonged because BB ingestion is often unwitnessed, and symptoms are non‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 More recently, studies from around the world have shown an increase in BB ingestion during the COVID-19 pandemic likely in part due to children being home and caregivers who must divide their attention between childcare and work-from-home duties. 7,8,18,19 Oesophageal impaction times are often prolonged because BB ingestion is often unwitnessed, and symptoms are non-specific. Ninety-two percent of fatalities and 56% of major complications occurred after unwitnessed ingestions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations